Establishing a legal service for major trauma patients at a major trauma centre in the UK. Issue 9 (9th June 2017) - Seligman, William H; Thompson, Julian; Thould, Hannah E; Tan, Charlotte; Dinsmore, Andrew; Lockey, David J
Abstract : Background: Major trauma causes unanticipated critical illness and patients have often made few arrangements for what are sudden and life-changing circumstances. This can lead to financial, housing, insurance, legal and employment issues for patients and their families. A UK law firm worked with the major trauma services to develop a free and comprehensive legal service for major trauma patients and their families at a major trauma centre (MTC) in the UK. Methods: In 2013, a legal service was established at North Bristol NHS Trust. Referrals are made by trauma nurse practitioners and it operates within a strict ethical framework. A retrospective analysis of the activity of this legal service between September 2013 and October 2015 was undertaken. Results: 66 major trauma patients were seen by the legal teams at the MTC. 535 hours of free legal advice were provided on non-compensation issues—an average of 8 hours per patient. Discussion: This initiative confirms a demand for the early availability of legal advice for major trauma patients to address a range of non-compensation issues as well as for identification of potential compensation claims. The availability of advice at the MTC is convenient for relatives who may be spending the majority of their time with injured relatives in hospital. More data are needed to establish the rehabilitation and health effects of receiving non-compensation advice after major injury; however, the utilisation of this service suggests that it should be considered at the UK MTCs.